Research on Automated System Testing in Web Site Applications - qizi, Yo'ldoshova Hilola Baxtiyor (Researchparks Publishing, 2023)
The article discusses technology and methodology for automating the process of testing Web site applications and system programs for adaptation of applications to technological processes were considered. Developers and automation professionals are currently going through popular boom times. In the process of software development and testing, not only developers and testers work in the team, but business professionals who identify a number of changes when new versions of software products are released will be able to perform these studies. In technical systems, an integral part of the release is automated test creation. It is the use of automation tools. An object-oriented approach to project implementation, a set of standard tools to ensure construction processes and debugging programs, connecting auxiliary libraries for the used programming language (C++, C#, Java, etc. programming languages); check system versions, automation project and software product storage options are considered. Despite the proliferation of quality assurance tools and experts in technological processes, IT software testing is important. Development and security of software systems are at the forefront of the Internet space. Complexity and difficulties of testing loads experts into test automation technology with multiple steps and end-to-end calls. In the system studies have been conducted for higher levels of management and control. A clear demonstration of automation in this article approaches and development approaches are important. Research results clearly show this automating software testing areas is a new strategy poised to transform usability, security ensures the efficiency and reliability of current and future software applications. Testing is a very important activity. In the process of software development, it is necessary to eliminate defects on the spot. It consists of the process of checking and modifying the source code. Effective testing ensures high quality and software ensures excellence. This article discusses the important and vital issue of software testing. Testing can be done manually and using automated systems. This technique has its own advantages and disadvantages. The main objective of this study is to identify and then analyze the weaknesses and strengths of automation techniques and will consist of testing web applications that are currently in rapid development. Research itself, to implement information work was carried out on the stages of development of this topic (articles, reports, automation tools themselves). As a result, the authors draw conclusions about the further directions for the development of web application testing, identify the advantages and the problem existing solutions and insufficiently developed processes are identified.